Call me Ishmaelle - Guo, Xiaolu, 1973- (Black Cat, an imprint of Grove Atlantic, 2026)
"1843. Ishmaelle is born in a small village on the stormy Kent coast where she grows up swimming with dolphins. After her parents and infant sister die, her brother, Joseph, leaves to find work as a sailor. Abandoned and desperate for a life at sea, Ishmaelle disguises herself as a cabin boy and travels to New York. Nearly twenty years later, as the American Civil War breaks out, Ishmaelle boards the Nimrod, a whaling ship led by the obsessive Captain Seneca, a Black free man of heroic stature who is haunted by a tragic past. Here, she finds protectors amidst the bloody male violence of whaling and discovers a mysterious bond between herself and the white whale who claimed Seneca's leg. Built on the bones of Melville's classic, Call Me Ishmaelle is a dynamic new tale, imbued with a diverse, swashbuckling crew--from a Polynesian harpooner to a Taoist Monk-and a powerful exploration of human nature, gender, and the nature of home"-- Provided by publisher.